Analisis Nilai Tambah Pengolahan Gula Semut Pada Umkm Guleku di Desa Tuana Tuha - Siska Siska; Candra Catur Nugroho; Pinto Rukmi Handayani; Syahruddin syahruddin (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Palm trees have a high economy because almost all of them can provide financial benefits. One of them is in Kenohan District, namely in Tuana Tuha Village, developing one of its economic potentials, namely by producing raw materials derived from palm sap. Tuana Tuha, Kenohan District. Then to find out what are the obstacles faced by the business. This research was carried out in May 2022 in MSMEs processing ant sugar. This study uses primary and secondary data obtained from business owners through direct interviews using questionnaires, and secondary data obtained through literature that has a relationship with this research. The method used in this study is the analysis of the added value of the Hayami method (1987) with the help of the Microsoft Office Excel 2013 computer program. The results of this study indicate that the added value of processing palm sugar products in May 2022 is Rp. 23,003,-kg with an added value ratio of 0.38 percent, and the profit earned on the Guleku SMEs from processing 1 Kilogram of palm sugar raw materials into palm sugar is Rp. 22.003,-kg with a profit rate of 0.37 percent. The obstacle faced in this ant sugar business is the weather factor.